Drastic Improvements in Air Quality in Ecuador during the COVID-19 Outbreak - Rasa Zalakeviciute; Renne Vasquez; Daniel Bayas; Adrian Buenano; Danilo Mejia; Rafael Zegarra; Valeria Diaz; Brian Lamb (Aerosol and Air Quality Research)
Abstract In the beginning of 2020, the global human population encountered the pandemic of novel coronavirus disease 2019 (COVID-19). Despite social and economic concerns, this epidemiologic emergency has brought unexpected positive consequences for environmental quality as human activities were reduced. In this paper, the impact of restricted human activities on urban air quality in Ecuador is investigated. This country implemented a particularly strict set of quarantine measures at the very dawn of the exponential growth of infections on March 17, 2020. As a result, significant reductions in the concentrations of NO2 (–68%), SO2 (–48%), CO (–38%) and PM2.5 (–29%) were measured in the capital city of Quito during the first month of quarantine. This large drop in air pollution concentrations occurred at all the monitoring sites in Quito, serving as a valuable proof of the anthropogenic impact on urban air quality. The spatial evolution of atmospheric pollution using observed surface and satellite data, showed different results for the two major cities: Quito and Guayaquil. While the population in Quito adhered to the quarantine measures immediately, in the port city of Guayaquil, quarantine measures were slow to be adopted and, thus, the effect on air quality in Guayaquil occurred more slowly. This lag could have a considerable cost to the mortality rate in the port city, not only due to the spread of the disease but also due to the poor air quality. Overall, the air quality data demonstrate how quickly air quality can improve when emissions are reduced.